Efficient Synthesis of Calix[4]phyrins Catalyzed by Amberlyst™-15 and Its Noncovalent Interactions with Neutral Molecules - Singhal, Anchal; Chauhan, Shive M.S. (Current Organic Chemistry, 2017)
Background: Calix[4]phyrins are fascinating hybrid molecules that contain a mixture of sp2- and sp3- hybridized meso-carbon bridges and bear analogy to both porphyrins and calix[4]pyrroles and hence find use in various applications. Various methods have been reported in the literature for the synthesis of calix [4] phyrins but with disadvantages of using corrosive acids and getting mixture of products, the separation of which is tedious. Hence, mild synthetic route for synthesis of calix[4]phyrins is highly desirable. Objective: Mild and efficient synthesis of calix[4]phyrins and their binding studies with neutral molecules are presented in this manuscript. Methods: Various functional calix[4]phyrins were synthesized by the condensation reaction of acetone with various functional dipyrromethanes catalyzed by reusable heterogeneous Amberlyst™-15 at ambient temperature followed by oxidation with DDQ. Different solvents were used as reaction medium to optimize the yield of calix[4]phyrins. Non-covalent interactions of 5,15-di-(p-methoxyphenyl)-10,10,20,20-tetramethylcalix[4] phyrin with p-nitrophenol and p-nitrotoluene were studied using UV-Vis spectrophotometer. Results: Amberlyst™-15 acts as an efficient catalyst for the synthesis of calix[4]phyrins in moderate to good yields. Dichloromethane was found to be best suitable solvent for the synthesis of calix[4]phyrins. In the UVVis studies of 5,15-di-(p-methoxyphenyl)-10,10,20,20-tetramethylcalix[4]phyrin with p-nitrophenol as well as with p-nitrotoluene, two clear isobestic points were observed in each spectra showing that two molecules are interacting with each other. Conclusion: An efficient method is developed to synthesize a parallel library of calix[4]phyrins. Non-covalent interactions between 5,15-di-(p-methoxyphenyl)-10,10,20,20-tetramethylcalix[4]phyrin as neutral donor and aromatic nitro compounds as neutral acceptors are established by UV-Vis studies.
Keywords: calix[4]phyrin